STUDENTS’ PERCEPTION OF TEACHER’S BILINGUAL LANGUAGE USE IN AN ENGLISH CLASSROOM - Yusi Nursanti (Journal of English and Education, 2016)
This study aims to investigate the perception of students toward the use of two languages of instruction (English and Indonesian) by the teacher in an English classroom and to find out its benefits for students in learning English. This study employed qualitative approach as a basic framework of study with a case study method. The participants of this study were 50 students of 7th grade at a junior high school in Bandung Regency. The data from questionnaire were analysed based on Likert scale by Ockert (2005) for investigating students’ perception and semi-structured interview by Fraenkel and Wallen (2012) for finding the benefits of teacher’s bilingual language use for students in learning English. This study reveals that (1) students show their positive perceptions to the use of bilingual language done by the teacher as language instruction in their English classroom; (2) there are six benefits of teacher’s bilingual language use for students in learning English; making them easy to understand what the teacher explained in English lesson, feel comfortable during the class, easy to understand new vocabularies in English, help them to do exercises, help them to ask and answer something during the class, and help them to read something in English correctly. Hopefully, the findings would give a great contribution to the enrichment of the best classroom language instruction should be used by the teacher in an English language learning classroom especially for teaching the students at low level of English proficiency and where English is existed as a foreign language (EFL).